Dynamics of Bt cotton Cry1Ac protein content under an alternating high temperature regime and effects on nitrogen metabolism - Xiang ZHANG; Qiu-zhi RUI; Pan-pan LIANG; Chen-hua WEI; Guo-qiang DENG; Yuan CHEN; Yuan CHEN; Zhao-di DONG; De-hua CHEN (Journal of Integrative Agriculture, 2018)
This study was conducted to investigate the effects of alternating high temperature on Cry1Ac protein content on Bt cotton cultivars Sikang 1 (SK-1, a conventional cultivar) and Sikang 3 (SK-3, a hybrid cultivar). In 2011 and 2012, cotton plants were subjected to high temperature treatments ranging from 32 to 40°C in climate chambers to investigate the effects of high temperature on boll shell insecticidal protein expression. The experiments showed that significant decline of the boll shell insecticidal protein was detected at temperatures higher than 38°C after 24 h. Based on the results, the cotton plants were treated with the threshold temperature of 38°C from 6:00 a.m. to 6:00 p.m. followed by a normal temperature of 27°C during the remaining night hours (DH/NN) in 2012 and 2013. These treatments were conducted at peak boll growth stage for both cultivars in study periods of 0, 4, 7, and 10 d. Temperature treatment of 32°C from 6:00 a.m. to 6:00 p.m. and 27°C in the remaining hours was set as control. The results showed that, compared with the control, after the DH/NN stress treatment applied for 7 d, the boll shell Cry1Ac protein content level was significantly decreased by 19.1 and 17.5% for SK-1 and by 15.3 and 13.7% for SK-3 in 2012 and 2013, respectively. Further analysis of nitrogen metabolic physiology under DH/NN showed that the soluble protein content and the glutamic pyruvic transaminase (GPT) activities decreased slightly after 4 d, and then decreased sharply after 7 d. The free amino acid content and the protease content increased sharply after 7 d. The changes in SK-1 were greater than those in SK-3. These results suggest that under DH/NN stress, boll shell Cry1Ac protein content decline was delayed. Reduced protein synthesis and increased protein degradation in the boll shell decreased protein content, including Bt protein, which may reduce resistance to the cotton bollworm.